Small bowel obstruction secondary to uterine fibroids: a case presentation - Antzoulas, Andreas; Verras, Georgios-Ioannis; Leivaditis, Vasileios; Papatriantafyllou, Athanasios; Tchabashvili, Levan; Benetatos, Nikolaos; Mulita, Francesk (Menopause Review/Przegląd Menopauzalny, 2024)
Small bowel obstruction (SBO) is a serious condition with distinct symptoms such as constipation, vomiting, and abdominal distension. It is commonly caused by well-recognised factors. Recent advancements in imaging techniques and minimally invasive procedures have significantly improved our ability to accurately select patients for surgical intervention and promptly identify common SBO causes. Nonetheless, it is crucial to recognise that diagnosing rare SBO causes remains a challenge. We present a rare case of mechanical bowel obstruction caused by massive uterine fibroids in a 44-year-old woman. Large uterine fibroids can cause mechanical small intestine obstruction, although this is not a common cause. Diagnostic imaging, particularly computed tomography, plays a crucial role in diagnosing and determining appropriate management plans. Accurate monitoring and imaging can lead to improved patient outcomes by avoiding unnecessary surgical intervention and reducing morbidity and mortality rates. Treatment options include both medical and surgical methods. Both approaches have proven effective, with surgical procedures being the last resort if medical treatments are unsuccessful. The accuracy and efficacy of these surgical methods have shown promising results and significant prognostic benefits. It is critical to identify and report rare causes of bowel obstruction to improve future recognition and enhance patient outcomes.